Odpowiedź :
Odpowiedź:
[tex]P=\frac{1}{2} (b+3+5)\cdot(a+3)-\frac{1}{2}(b+3)\cdot a\\\\P=\frac{1}{2}(b+8)\cdot(a+3)-\frac{1}{2}ab-\frac{3}{2}a\\\\P=\frac{1}{2} (ab+3b+8a+24)-\frac{1}{2}ab-\frac{3}{2}a\\\\P=\frac{1}{2}ab+\frac{3}{2}n+4a+12-\frac{1}{2}ab-\frac{3}{2} a\\\\\boxed{P=2\frac{1}{2} +1\frac{1}{2} +12}[/tex]
Szczegółowe wyjaśnienie:
b)
[tex]P = \frac{1}{2}(b+3+5)\cdot(a+3) -\frac{1}{2}(b+3)\cdot a\\\\P = \frac{1}{2}(b+8)\cdot(a+3) -\frac{1}{2}ab-\frac{3}{2}a\\\\P = \frac{1}{2}(ab+3b+8a+24)-\frac{1}{2}ab-\frac{3}{2}a\\\\P = \frac{1}{2}ab+\frac{3}{2}b + 4a + 12 - \frac{1}{2}ab-\frac{3}{2}a[/tex]
[tex]P = 4a-\frac{3}{2}a +\frac{1}{2}ab - \frac{1}{2}ab+\frac{3}{2}b + 12\\\\P = 4a -1,5a +1,5b+12\\\\\boxed{P = 2,5a+1,5b+12}[/tex]